Análisis y elaboración de una base de datos realizada según el censo de equipos electrónicos para uso médico del hospital militar hd-ii-de "libertad" - Yapur Auad, Miguel Eduardo (2009)
The present work is based on a survey to determine the level of service of the Military Hospital HD-II-DE "Libertad", that gives to the military men, relatives and individuals based on procedures, specifications and safety policies related to electrical, mechanical, environmental, biological, electromagnetic and radioactive fields; and, in a census of electronic equipments for medical use, with the purpose of determining the level of equipment of the hospital in the different areas and the services that this one can offer to the community. This survey serves also to determine the common reasons for which, the electronic equipment for medical use, suffer damages.